2006
DOI: 10.1111/j.0014-3820.2006.tb01886.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Phylogeny of Alpheid Shrimps: Parallel Preadaptation and the Origin of a Key Morphological Innovation, the Snapping Claw

Abstract: Abstract. The Alpheidae-possibly the most diverse family of recent decapod crustaceans-offers attractive opportunities to study the evolution of many intriguing phenomena, including key morphological innovations like spectacular snapping claws, highly specialized body forms, facultative and obligate symbioses with many animal groups, and sophisticated behaviors like eusociality. However, studies of these remarkable adaptations remain hampered by insufficient phylogenetic information. We present the first phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 59 publications
2
81
0
Order By: Relevance
“…Although the drag forces in terrestrial systems are often negligible, the aquatic appendages of dragonfly larvae, snapping shrimp and mantis shrimp, for example, necessarily incur substantial drag (Anker et al, 2006;McHenry et al, 2012;Tanaka and Hisada, 1980;Versluis et al, 2000). Therefore, relationships among the parameters that influence drag have the potential to inform interpretations of morphological diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Although the drag forces in terrestrial systems are often negligible, the aquatic appendages of dragonfly larvae, snapping shrimp and mantis shrimp, for example, necessarily incur substantial drag (Anker et al, 2006;McHenry et al, 2012;Tanaka and Hisada, 1980;Versluis et al, 2000). Therefore, relationships among the parameters that influence drag have the potential to inform interpretations of morphological diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The result shows that Aspergillus, Penicillum and Fusarium species are higher in number on the shrimp; this is in line with the study carried out by Lidiane et al, (2011), [13], who reported that the highest genera of fungi that attack Litopenaeus vannamei shrimps are Aspergillus, Fusarium and Penicillin species.This is also in line with Obire et al, (2011), [14], that reported to isolate Penillium, Fusarium, Aspergillus, Rhizopus, and Mucor from shrimp before and after detoriation. Most of the fungi species isolated have been separated as mycoses agent in human causing skin infections, Aspergillosis, liver furor, fungal balls in the lungs ,chronic productive cough and haemoptyes bronchial asthma, infection of the ear or paranasal sinuses, necrosis and eventual abscesses and varicose dermatitis, a chronic human mycosis [15].…”
Section: Discussionmentioning
confidence: 99%
“…With a total of 14 species, the alpheids were the most prominent family with respect to species richness. Indeed, alpheid shrimps are highly diverse in tropical regions, where they occupy a wide variety of marine and estuarine habitats, living on various types of bottom and in association with other phyla of invertebrates as well as with fish (Anker et al 2006b). In contrast, the richness of palaemonids and hippolytids is proportionally higher in shallow-water environments in temperate areas, especially in areas covered with vegetation (Hooks et al 1976;Gore et al 1981;López de la Rosa et al 2002;Glancy et al 2003).…”
Section: Discussionmentioning
confidence: 99%